Edukasi P3K Pada Kasus Tersedak Pada Wali Murid Di Pos Paud Tunas Jati Desa Kedungjati Kecamatan Sempor - Eni Indrayani; Eka Novyriana; Juni Sofiana; Khulasoh (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Tunas Jati Paud Pos, Kedungjati Village, Sempor District, is one of the Pauds in a mountainous area far from the district town center.This community service activity was carried out to improve the understanding and skills of parents at Tunas Jati Early Childhood Education Post in managing choking.This activity began with initial socialization and discussions with partners and preparation of infrastructure. The material is provided through socialization or counseling methods and choking demonstrations.Monitoring and evaluation of activities is seen from three indicators including input, process and output indicators.In terms of input, this activity was successful as planned and was attended by 30 participants who were parents of Pos Paud Tunas Jati students.Judging from the process indicators, participants appeared enthusiastic about participating in all activities from start to finish.This activity also succeeded in fulfilling the output indicators with the majority of activity participants (>90%) successfully answering all post-test questions correctly.It is hoped that all participants will be able to apply the knowledge and skills gained through the activity and independently disseminate the material to other residents.